Antifungal activity of selected plant leaves crude extracts against a pepper anthracnose fungus, Colletotrichum capsici (Sydow) butler and bisby (Ascomycota: Phyllachorales) - Johnny, Lucy; Yusuf, Umi Kalsom; Nulit, Rosimah (Academic Journals, 2011)
The antifungal activities of the leaves extract of 15 selected medicinal plants; Alpinia galanga (L.) Willd., Alstonia spatulata Blume., Annona muricata L., Blechnumorientale L., Blumea balsamifera L., Centella asiatica L., Dicranopteris linearis(Burm. f.) Underw., Dillenia suffruticosa (Griff ex Hook.f. and Thomson) Martelli, Litsea garciae Vidal., Melastoma malabathricum L., Momordica charantia L.,Nephrolepis biserrata (Sw.), Pangium edule Reinw., Piper betle L. and Polygonum minus Huds., were evaluated on the plant pathogenic fungus, Colletotrichum capsici which was isolated from chilli. The antifungal assay was carried out in potato dextrose media in five different treatments, which were distilled water as the negative control, crude extract of leaves in methanol, chloroform, acetone and Kocide 101 as the positive control. They were carried out in three replicates. The two-way analysis of variance (ANOVA) was carried out on all the data to justify the difference between critical difference (CD) of mean (P = 0.05) and coefficient of variation (CV %) in terms of mean percent reduction in colony diameter, sporulation and minimum inhibitory concentration (MICs) of C. capsici to take statistical decisions. Crude extract of P. betle in all the solvents was found to be the most effective and exhibited the highest antifungal activities. Crude extract of P. betle in methanol inhibited 85.25% of radial growth of C. capsici followed by 78.53% leaves crude extract in chloroform and 73.58% leaves crude extract in acetone at the concentration of 10 µg/ml (p < 0.05). The exact concentrations that had definite potential to fully restrict the growth (100% inhibition) of C. capsici (MIC) by P. betlewas 12.50 µg/ml in methanol, 17.50 µg/ml in chloroform and 15.00 mg/ml in acetone. The sporulation assay also revealed that, P. betle leaves crude extracts showed the highest inhibition of spore germination rate of C. capsici overall at the concentration of 10 µg/ml; with 80.93% inhibition by leaves crude extracts in methanol, 74.09% by leaves crude extracts in chloroform and 72.91% by leaves crude extracts in acetone. Concentration of plant leaves crude extracts that inhibited 50% or more of the radial growth and sporulation was considered as effective (LC ≥ 50). As a conclusion, the leaf crude extracts that exhibited effectiveness by showing more than 50% inhibition against C. capsici should be considered for further evaluation. P. betle leaf crude extracts was the most effective in inhibiting the fungus respectively and thus, exhibited the highest potential as a new leading biofungicide in the agriculture field.